GC-MS Analysis of Various Phytoestrogens in Health Functional Foods - Kim, Yu Ra; Pyo, Hee Soo; Chung, Bong Chul; Moon, Myeong Hee; Lee, Jeongae (대한화학회, 2017)
This study aimed to measure phytoestrogen contents in health functional foods (HFFs) to alleviate menopausal symptoms that are commercially available in South Korea. A sensitive and selective method using gas chromatography-mass spectrometry (GC-MS) for the monitoring of 21 phytoestrogens was developed and fully validated. Phytoestrogens were extracted by liquid-liquid extraction using methyl tert-butylether as the solvent. Food samples were enzymatically hydrolyzed with beta-glucuronidase/arylsulfatase. Before GC-MS, the analytes were derivatized to their trimethylsilyl derivatives by incubation with N,O-bis(trimethylsilyl)trifluoroacetamide with 1% trimethylchlorosilane for 30min at 80 degrees C. The calibration curves showed good linearity (r(2)>0.99) in the range of interest for each analyte. The limits of detection and quantification of the 21 phytoestrogens were in the ranges of 0.5-20 and 1-50ng/mL, respectively. The intra- and inter-day precisions were all below 15.7%. These multivariate procedures were efficient in determining the optimal conditions using peak heights as responses.